PERBEDAAN PENANGANAN PERILAKU SISWA YANG MENGGANGGU DALAM PROSES PEMBELAJARAN KLASIKAL SEKOLAH MENENGAHOLEH GURU LAKI-LAKI DAN PEREMPUAN - Amirah Diniaty (Marwah: Jurnal Perempuan, Agama dan Jender, 2016)
Female teacher tends to recognize irritating behavior of the pupils (Prilaku Siswa yang Menggangu/PSM) in learning process compared with male teacher. However, the difference is less significance. The most dominant form of PSM happening to the pupil is attention seeker in which the pupil talk in classroom during the learning process. Even though PSM is rare, it still requires an appropriate measure conducted by the teacher toward the PSM in order to lessen the frequency. The finding of this research shows that male teacher stricter than female teacher in handling PSM.